The complete chloroplast genome of Cotyledon tomentosa Harv. - Yanfeng He; Hongting Ma; Ruinan Wang; Xiangyun Gai; Pengcheng Lin; Jiaqi Zhang; Yingfang Shen (Mitochondrial DNA. Part B. Resources, 2021)
Cotyledon tomentosa Harv. is a well-known succulent plant that have important ornamental and economic value. In this study, we release and detail the complete chloroplast genome sequences of C. tomentosa. The whole chloroplast genome was 149,729 bp in length and comprised 131 genes, including 84 protein-coding genes, 37 tRNA genes, eight rRNA genes. The C. tomentosa. chloroplast genome had a GC content of 38.23%. Phylogenetic analysis based on the complete chloroplast genomes showed that C. tomentosa had a close relationship with Kalanchoe tomentosa, Bryophyllum daigremontianum and Kalanchoe fedtschenkoi.